Peace and Discourse: The Construction of the Costa Rican Peaceful Identity between 1978 and 1990 - Astorga Sánchez, Leonardo (2021)
The main objective of this paper is to carry out an analysis of how the concept of peace was used during three Costa Rican presidential administrations between 1978 and 1990. Taking the History of Concepts as a starting point, it is investigated how each of the presidents Carazo, Monge and Arias They used Peace to legitimize their political projects, their experiences and aspirations and also how through their speeches the already traditional peaceful identity of Costa Rica was strengthened, reinforcing in a context of crisis and the Cold War the so-called Costa Rican exceptionality.